Assessment of design parameters influencing seismic collapse performance of buckling-restrained braced frames. Issue 113 (October 2018) - Zaruma, Santiago; Fahnestock, Larry A.
Abstract: Buckling Restrained Braced Frames (BRBFs) are widely used as seismic force-resisting systems due to their significant ductility and energy dissipation capacity. However, owing to their modest overstrength and relatively low post-yield stiffness, BRBFs subjected to seismic loading may be susceptible to concentrations of story drift and global instability triggered by P -∆ effects. Due to the use of simplistic methods that are based on elastic stability, current code-based design provisions do not address seismic stability rigorously and do not consider the unique inelastic characteristics of different systems. Supplemental strategies may be used to prevent undesirable seismic response of BRBFs, such as story drift concentration and large residual drift. This study employed the FEMA P695 framework to evaluate the response of BRBFs designed according to current codes in the United States and to study the effect on seismic stability of three additional parameters: BRBF column orientation, gravity column continuity, and dual systems. Results from nonlinear static and dynamic analyses provide insight into seismic behavior, and collapse performance evaluation quantifies the relative performance of various BRBF designs and supplemental strategies for enhancing seismic stability. Highlights: This study employed nonlinear analyses to evaluate seismic stability of BRBFs. Code-based stability design requirements do not address post-yield stiffness. BRBF column orientation significantly influences seismic response. Gravity column continuity significantly influences seismic response. BRBF-SMRF dual systems demonstrated superior seismic response.